2012
DOI: 10.1002/ajmg.b.32093
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Genetic Heterogeneity of Depression Through Age at Onset

Abstract: Genome-wide studies in major depression have identified few replicated associations, potentially due to heterogeneity within the disorder. Several studies have suggested that age at onset (AAO) can distinguish sub-types of depression with specific heritable components. This paper investigates the role of AAO in the genetic susceptibility for depression using genome-wide association data on 2,746 cases and 1,594 screened controls from the RADIANT studies, with replication performed in 1,471 cases and 1,403 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
2
27
1
Order By: Relevance
“…Our patients were mostly elderly (age >60 years, 74.2%), and a large portion of them had late-onset illness (age of first onset >60 years, 45.5%). Several studies have suggested that the age at onset can vary in different subtypes of depression, especially in terms of heritability 3738. In addition, previous studies reported that proinflammatory cytokines increase in healthy elderly people,394041 although, we could not find a significant relationship between age, age on onset and sCD40L in our study subjects.…”
Section: Discussioncontrasting
confidence: 83%
“…Our patients were mostly elderly (age >60 years, 74.2%), and a large portion of them had late-onset illness (age of first onset >60 years, 45.5%). Several studies have suggested that the age at onset can vary in different subtypes of depression, especially in terms of heritability 3738. In addition, previous studies reported that proinflammatory cytokines increase in healthy elderly people,394041 although, we could not find a significant relationship between age, age on onset and sCD40L in our study subjects.…”
Section: Discussioncontrasting
confidence: 83%
“…A genome-wide association study has examined AO of MD as a quantitative trait (in European samples with mean AO of ∼20 years of age, N < 2,000 cases and controls). 28 While specific genome-wide hits did not replicate, results did suggest that common genetic variants may explain a large portion of the variance in AO in European samples (55%, p =.02). Finally, in a report by the Psychiatric Genomics Consortium working group, polygenic score analyses across mixed-ancestry samples suggested that earlier-onset MD is genetically more similar to major psychiatric disorders like schizophrenia and bipolar disorder than is adult-onset MDD.…”
Section: Introductionmentioning
confidence: 86%
“…Using molecular data on common variants, preliminary research thus far has found a marginally significant single nucleotide polymorphism (SNP)-based heritability estimate of .17 (P = .04 ;Ferentinos et al, 2015) for presence/absence of early AO. A genome-wide association study has examined AO of MD as a quantitative trait (in European samples with mean AO of ∼20 years of age, N < 2,000 cases and controls; Power et al, 2012). Although specific genome-wide hits did not replicate, results did suggest that common genetic variants may explain a large portion of the variance in AO in European samples (55%, P = .02).…”
Section: Introductionmentioning
confidence: 99%
“…Of interest for this study, GREML demonstrated that common SNPs explained 32% of the variance in depression severity (Lubke et al, 2012) and 51% of the variance in age at onset of MDD (Power et al, 2012). Furthermore, common SNPs accounted for 42% of the variance in pharmacological treatment response of patients with MDD (Tansey et al, 2013).…”
Section: Introductionmentioning
confidence: 99%